Community paramedic point of care testing: validity and usability of two commercially available devices - Blanchard, Ian E. (BMC Emerg Med, 2019)
BACKGROUND: Community Paramedics (CPs) require access to timely blood analysis in the field to guide treatment and transport decisions. Point of care testing (POCT), as opposed to laboratory analysis, may offer a solution, but limited research exists on CP POCT. The purpose of this study was to compare the validity of two devices (Abbott i-STAT® and Alere epoc®) by CPs in the community. METHODS: In a CP programme responding to 6000 annual patient care events, a split sample validation of POCT against traditional laboratory analysis for seven analytes (sodium, potassium, chloride, creatinine, hemoglobin, hematocrit, and glucose) was conducted on a consecutive sample of patients. The difference of proportion of discrepant results between POCT and laboratory was compared using a two sample proportion test. Usability was analysed by survey of CP experience, a linear mixed effects model of Systems Usability Scale (SUS) adjusted for CP clinical and POCT experience, an expert heuristic evaluation of devices, a review of device-logged errors, and coded observations of POCT use during quality control testing. RESULTS: Of 1649 episodes of care screened for enrollment, 174 required a blood draw, with 108 episodes (62.1%) enrolled from 73 participants. Participants had a mean age of 58.7 years (SD16.3); 49% were female. In 4 of 646 (0.6%) comparisons, POCT reported a critical value but the laboratory did not; with no statistically significant (p = 0.323) difference between i-STAT® (0.9%;95%CI:0.0,1.9%) compared with epoc® (0.3%;95%CI:0.0,0.9%). There were no instances of the laboratory reporting a critical value when POCT did not. In 88 of 1046 (8.4%) comparisons the a priori defined acceptable difference between POCT and the laboratory was exceeded; occurring more often in epoc® (10.7%;95%CI:8.1,13.3%) compared with i-STAT® (6.1%;95%CI:4.1,8.2%)(p = 0.007). Eighteen of 19 CP surveys were returned, with 11/18 (61.1%) preferring i-STAT® over epoc®. The i-STAT® had a higher mean SUS score (higher usability) compared with epoc® (84.0/100 vs. 59.6/100; p = 0.011). There were no statistically significant differences in device logged errors between i-STAT® and epoc® (p = 0.063). CONCLUSIONS: CP programmes can expect clinically valid results from POCT. Device usability assessments should be considered with any local implementation as the two POCT systems have different strengths. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12873-019-0243-4) contains supplementary material, which is available to authorized users.